Investigating lung function gene GSTCD using gene targeting in human and mouse systems - Probert, Kelly (2016)
Respiratory diseases are a significant global health concern and burden, with one of the major respiratory diseases causing a decline in lung function being chronic obstructive pulmonary disease (COPD). Critically, current therapies have limited impact. Recently, single nucleotide polymorphisms at chromosome locus 4q24 have been identified as associated with the lung function measure forced expiratory volume in 1 second and COPD, specifically identifying the gene Glutathione S-transferase C-terminal domain containing (GSTCD) as a viable candidate gene. Data indicate that GSTCD or associated biological pathways may be a potential target for interventions to alleviate COPD. Further analysis into the pathways and phenotypic effects of this gene may aid our understanding of the mechanisms by which GSTCD is associated with and influences lung function and COPD.